Simulacrum and Mystical Logic in the Commodification of Communication in the Narrative of the Film "Ghost In The Cell"” - A.Yudo Triartanto; Tuty Mutiah; Syarif Fitri (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
This research focuses on supernatural entities, religion, satire, parody, and codes, through simulacrum and mystical logic in the commodification of communication in the narrative of the horror-thriller genre film entitled "Ghost in the Cell" which takes place in Labuhan Angsana prison. In this film, it is narrated that prison is not only filled with evil and greedy people, but also people who are actually innocent. In prison there is also an invisible ghost figure, then incarnates and duplicates itself to resemble a potential victim who will be killed sadistically and aesthetically. This research uses the concepts and theories of Commodification (Vincent Mosco), Simulacrum (Jean Baudrillard), Intertextuality (Julia Kristeva), and Binary Opposition Narrative Analysis (Vladimir Propp and Claude Levi-Strauss). The use of several concepts and theories to reveal the entity and narrative of the film contained in the characters and a number of scenes. The results of the study show that simuacrum and mystical logic in the horror genre continue, when an invisible ghost enters someone's body and appears, and presents something that is not real to be real (simulacrum) which is arranged into a narrative (intertextuality), and is represented functionally by the characters - a binary opposition narrative structure - as an attraction and interest for the majority of the audience through capitalist logic (communication commodification) and mystical logic.